An exploration of the educational experiences of high-achieving Somali students in London schools - Garre, Mohamud Y. (2022)
This thesis focuses on Somali students in London who achieved better GCSE (General Certificate of Secondary Education) results than is usual for their ethnic group. In general, the educational achievement of Somali children in the UK is a matter of concern. Recent statistics show that only 34 percent of Somali students gain pass grades at GCSE level. A combination of factors can explain this: many in the Somali community are refugees from conflict; they come from a country where the average level of education is low; they live in poverty; parents often do not speak good English or understand the school system. Nevertheless, some students do achieve better educational results. The research set out to explore the educational experiences of seven higher achieving students by generating life grids and by interviewing the students and their parents in their homes where ethnographic notes were made.